(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aimed to identify artificial intelligence and its role in digital transformation in order to adapt to the requirements of the external environment. This research was applied in the Ministry of Education, where a number of general directorates were selected from it, which included the research field. The research variables (artificial neural network, expert systems, algorithms, machine learning) were also measured as dimensions of the independent research variable, and the dependent research variable was taken as a whole. In addition, a random sample was selected from the research community, represented by a number of workers in it, amounting to (80) workers. Data and information were taken from them through the questionnaire that was distributed to them as a whole, which was later analyzed by the statistical program (SPSS) in order to obtain the results, the most important of which was the existence of two correlations and a significant effect between the research variables. The researchers also recommended the necessity of employing artificial intelligence requirements in order to prepare all transactions digitally, aiming to facilitate administrative procedures in the organization under study.